2019
DOI: 10.3389/fimmu.2019.00900
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in Lung Transplantation

Abstract: Myeloid-derived suppressor cells (MDSC) are a heterogeneous group of immune cells from the myeloid lineage. MDSCs expand in pathological situations, such as chronic infection, cancer, autoimmunity, and allograft rejection. As chronic lung allograft dysfunction (CLAD) limits long-term survival after lung transplantation (LTx), MDSCs may play a role in its pathophysiology. We assessed phenotype and frequency of MDSCs in peripheral blood from lung transplant recipients and its relationship to post-transplant comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The expansion and functional importance of MDSC in noncancer pathogenic conditions have been recently recognized. MDSC numbers are imbalanced and they act as a downregulation mechanism of immune responses in many diseases, such as autoimmune diseases [79], transplantation [80, 81], and asthma [82, 83, 84].…”
Section: Pathogenesis Of Ibdmentioning
confidence: 99%
“…The expansion and functional importance of MDSC in noncancer pathogenic conditions have been recently recognized. MDSC numbers are imbalanced and they act as a downregulation mechanism of immune responses in many diseases, such as autoimmune diseases [79], transplantation [80, 81], and asthma [82, 83, 84].…”
Section: Pathogenesis Of Ibdmentioning
confidence: 99%
“…Of particular interest, monocytederived DCs, isolated from the peripheral blood of lung transplant patients without bronchiolitis obliterans syndrome, were found to have higher IDO expression, implicating the involvement of MDSCs (242). A recent clinical study focused on MDSCs, assessing their phenotype and frequency in peripheral blood from 20 lung transplant recipients and its relationship to post-transplant complications and immunosuppression (243). In detail, MDSCs were isolated from PBMCs and their functionality was assessed in vitro by their capability to block CD4 + and CD8 + T cell proliferation.…”
Section: Immunoregulatory Cells and Lung Transplantation In Ipfmentioning
confidence: 99%
“…Thus, there is robust and growing evidence that immunoregulatory cells play a pivotal role in allograft acceptance from both experimental and clinical science (247). Coming back to MDSCs, current data attribute the immunoregulatory properties of these cells mainly to two mechanisms of action upstream of T cells to shift the immune response towards peripheral tolerance: First, to their capacity to inhibit the proliferation of allogeneic T cells (243); Second, to their capacity of Treg induction (248,249). Interestingly, the impact of concomitant immunosuppressive therapy, to prevent allograft rejection, while at the same time acting on the immune cells in general, and MDSCs in particular, has also become a field of increasing research activities.…”
Section: Immunoregulatory Cells and Lung Transplantation In Ipfmentioning
confidence: 99%
“…In humans, MDSCs have been implicated as important regulators of tolerance in kidney and lung transplantation ( 46 , 107 , 137 , 138 ). CD14 + M-MDSCs expand in renal transplant patients following transplantation, and these MDSCs are highly efficient in suppressing the proliferation of CD4 + T cells in mixed leukocyte reactions and are also capable of expanding Tregs in vitro .…”
Section: Therapeutic Potential Of Regulatory Cell Types In Transplantmentioning
confidence: 99%
“…In vitro , the MDSCs isolated from these patients were capable of expanding Tregs and inhibiting production of IL-17 ( 107 ). In a study investigating the role of MDSCS in human lung transplantation, it was found that circulating MDSCs are increased in stable lung transplant recipients versus non-transplant controls, and that patients with chronic lung allograft dysfunction (CLAD) had lower levels of MDSCs compared to stable recipients ( 137 ). These findings in humans, combined with the successful use of adoptive MDSC transfer in animal models described above, suggest that adoptive transfer of MDSCs could prolong organ allograft survival and promote graft tolerance in humans.…”
Section: Therapeutic Potential Of Regulatory Cell Types In Transplantmentioning
confidence: 99%